How do you solve x^ { 2} + 12x = - 60?

2 Answers
May 8, 2017

Use the quadratic equation

Explanation:

First we need to add 60 to make the right-hand side 0:
x^2+12x+60=0
Since this quadratic equation is not factorable, we apply the quadratic equation:
x=(-12+-sqrt(12^2-4*1*60))/(2*1)
x=(-12+-sqrt(-96))/2
Since we cannot square root a negative value, we use i to denote sqrt(-1) as the imaginary number
x=-6+-(4isqrt(6))/2
x=-6+-2isqrt(6)
Therefore, our answers are x=-6+2isqrt(6) and x=-6-2isqrt(6)

May 8, 2017

x=-6+-isqrt(-24)

Explanation:

Give -

x^2+12x=-60

Let use completing the square method

x^2+12x+36=-60+36

(x+6)^2=-24

x+6=+-isqrt(-24)

x=-6+-isqrt(-24)